Impaired kidney function at ED admission: a comparison of bleeding complications of patients with different oral anticoagulants - Martin Müller (BMC Emergency Medicine, 2021)
Abstract Background Up to a fourth of patients at emergency department (ED) presentation suffer from acute deterioration of renal function, which is an important risk factor for bleeding events in patients on oral anticoagulation therapy. We hypothesized that outcomes of patients, bleeding characteristics, therapy, and outcome differ between direct oral anticoagulants (DOACs) and vitamin-K antagonists (VKAs). Methods All anticoagulated patients older than 17 years with an impaired kidney function treated for an acute haemorrhage in a large Swiss university ED from 01.06.2012 to 01.07.2017 were included in this retrospective cohort study. Patient, treatment, and bleeding characteristics as well as outcomes (length of stay ED, intensive care unit and in-hospital admission, ED resource consumption, in-hospital mortality) were compared between patients on DOAC or VKA anticoagulant. Results In total, 158 patients on DOAC and 419 patients on VKA with acute bleeding and impaired renal function were included. The renal function in patients on VKA was significantly worse compared to patients on DOAC (VKA: median 141 μmol/L vs. DOAC 132 μmol/L, p = 0.002). Patients on DOAC presented with a smaller number of intracranial bleeding compared to VKA (14.6% DOAC vs. 22.4% VKA, p = 0.036). DOAC patients needed more emergency endoscopies (15.8% DOAC vs, 9.1% VKA, p = 0.020) but less interventional emergency therapies to stop the bleeding (13.9% DOAC vs. 22.2% VKA, p = 0.027). Investigated outcomes did not differ significantly between the two groups. Conclusions DOAC patients were found to have a smaller proportional incidence of intracranial bleedings, needed more emergency endoscopies but less often interventional therapy compared to patients on VKA. Adapted treatment algorithms are a potential target to improve care in patients with DOAC.